Non-entity conceptualisation as an approach in social education - Michal Černý (Sociální Pedagogika)
The present theoretical study focuses on reconceptualising the ontological model applied in social pedagogy from an entity-oriented to a distributed model of a dynamically changing network. The paper demonstrates how the novel conceptualisation can address intricate social pedagogy scenarios, including career counselling, defining social pedagogy, environmental grief, identity formation and engagement with social pedagogy target groups or integrating artificial intelligence in teaching. The study aims to introduce this novel way of thinking and acting into social pedagogical theory and practice and demonstrate the advantages of abandoning the entity- oriented approach.